EVALUASI PENATALAKSANAAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DI PUSKESMAS KOTA BENGKULU - Susilo, Avrilya Iqoranny; Satibi, Satibi; Andayani, Tri Murti (JURNAL MEDIA KESEHATAN, 2020)
Health Chronic Disease Management Program (Prolanis) BPJS Health as a system of health services and proactive approach implemented in an integrated manner involving participants, health facilities and BPJS Health becomes an important factor because it becomes one of the indicators of the fulfillment of the commitment of service at puskesmas. This study aims to determine the management of Prolanis which includes membership, activities, availability of drugs and availability of funds Prolanis, knowing the barriers to the implementation of Prolanis and know the ratio of visits and quality of life of participants Prolanis. The research was conducted by descriptive method through interview technique, check list and WHOQoL questionnaire for quality of life measurement. Data retrieval used primary data by interviewing 40 informants and filling questionnaire on 262 participants of Prolanis. The secondary data was obtained from P-Care Puskesmas application. Analysis of the results of research was using descriptive analysis with narrative exposure accompanied by data tables. The results showed that from 20 Puskesmas 1 Puskesmas had not fulfilled the minimum requirement of Prolanis formation, 4 Puskesmas had not conducted gymnastic and educational activities, 2 Puskesmas did not implement pharmacy service standard for drug distribution Prolanis and 4 Puskesmas had not utilized Prolanis fund provided by BPJS Kesehatan. 50% in some puskesmas cause puskesmas to be in unsafe zone for assessment of capitation indicator. For measurement of quality of life of participants Prolanis obtained 95, 04% of respondents have good quality of life.